2019
DOI: 10.1029/2019gl084130
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Convective Self‐Aggregation in Idealized Models to Observed Moist Static Energy Variability Near the Equator

Abstract: Idealized convection‐permitting simulations of radiative‐convective equilibrium have become a popular tool for understanding the physical processes leading to horizontal variability of tropical water vapor and rainfall. However, the applicability of idealized simulations to nature is still unclear given that important processes are typically neglected, such as lateral water vapor advection by extratropical intrusions, or interactive ocean coupling. Here, we exploit spectral analysis to compactly summarize the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
1
13
1
Order By: Relevance
“…This effect, if it exists, may be related to the moisture-memory feedback as often discussed in attempt to interpret convective self-aggregation in numerical simulations (Held et al 1993;Tompkins 2001;Muller and Bony 2015). The importance of the advection term in the CMSE budget is in line with Bretherton and Khairoutdinov (2015), who showed that the advection accounts for the rapid (,4 days) growth of MSE at the earliest stage of aggregation, although at odds with Beucler et al (2019), who found that the advection damps the MSE variance at all spatial scales.…”
Section: Discussion and Summarysupporting
confidence: 59%
See 1 more Smart Citation
“…This effect, if it exists, may be related to the moisture-memory feedback as often discussed in attempt to interpret convective self-aggregation in numerical simulations (Held et al 1993;Tompkins 2001;Muller and Bony 2015). The importance of the advection term in the CMSE budget is in line with Bretherton and Khairoutdinov (2015), who showed that the advection accounts for the rapid (,4 days) growth of MSE at the earliest stage of aggregation, although at odds with Beucler et al (2019), who found that the advection damps the MSE variance at all spatial scales.…”
Section: Discussion and Summarysupporting
confidence: 59%
“…The lack of evidence for any distinct effect of Q R on the aggregation may be understood in the context of the scale dependence of the aggregation processes. Beucler and Cronin (2019) and Beucler et al (2019) showed that the longwave effects favor a growth of large-scale aggregation with horizontal wavelengths of ;1000 km or larger, which exceeds the typical size of cloud clusters studied in the current analysis. Shortwave radiation, on the other hand, has the effect of shrinking the aggregation to smaller scales (500-2000 km) (Beucler and Cronin 2019).…”
Section: Discussion and Summarycontrasting
confidence: 45%
“…It is important to note that Equations and are approximations, as in reality the tendencies of CWV may depend on more than just CWV itself. By assuming that the evolution of CWV is given by its mean value in CWV space, we successfully capture the time evolution of the spatial‐mean CWV field but reduce the spatial variance of the CWV time tendencies by a factor 100 (as estimated using the Beucler et al., 2019, framework, not shown). Finally, note that it is possible to choose column moist static energy (MSE) instead of CWV as the order variable in Equation : In that case, Equation can be applied to the MSE tendencies of individual physical processes, which helps link our framework to the MSE budget framework extensively used by the self‐aggregation community (see Appendix for more details).…”
Section: Theorymentioning
confidence: 99%
“…advection, convection, radiation, and microphysics on water vapor. This led to an Eulerian view of this bimodality, in which the formation of large-scale moist and dry regions happens within a week to a month at the ∼1,000to 10,000-km scale through the interaction between CWV and radiation in the slowly rotating tropics (e.g., Beucler et al, 2019;Holloway & Woolnough, 2016;C. Muller & Bony, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…External forcing such as spatially varying SSTs, large-scale low-level convergence of trade winds (Back & Bretherton, 2009;Bretherton & Sobel, 2002;Lindzen & Nigam, 1987), and wind shear (Rotunno et al, 1988), which are not considered in the RCE framework, are known to promote the organization of convection in the tropics and may mask the effects of self-aggregation. Consequently, observational evidence of self-aggregation of convection or of its expected effects on climate has been sought (Beucler et al, 2019;Holloway et al, 2017;Tobin et al, 2012), but the importance of self-aggregation of convection in the presence of external forcing remains unclear.…”
Section: Introductionmentioning
confidence: 99%